Global, regional, and national burden of ovarian cancer due to high BMI, 1990–2021 and projections to 2050: a systematic analysis based on the global burden of disease 2021 study - Xu, Shuiqing; Fu, Xiaotong; Wang, Ming (Frontiers in Nutrition, 2026)
Using GBD 2021 data, this study quantifies the disease burden of ovarian cancer attributable to high BMI—encompassing mortality and disability-adjusted life years (DALYs)—across 204 countries/regions globally between 1990 and 2021. By analyzing temporal trends, we will identify regions with a significant increase in burden, providing a basis for formulating targeted prevention and control strategies. We also explore correlations between disease burden and socioeconomic indicators to assess how socioeconomic factors influence ovarian cancer incidence and prognosis. In addition, we will analyze the roles of aging, population structure changes, and epidemiological factors in the burden of ovarian cancer caused by high BMI, dissect differences between countries, and predict trends up to 2050. The results of this study will provide important references for public health policy formulation, rational resource allocation, and the prevention and control of ovarian cancer.